Pemberdayaan Keluarga terhadap Kualitas Hidup Lansia Hipertensi - Amaliyah, Eli; Aminah, Aminah; Lisnawati, Lisnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of family empowerment on the quality of life of the elderly in Banten. This study was conducted using a quasi-experimental design with two pre- and post-test groups at the Serang Health Center, Banten. The data collection process was repeated three times in both groups. The family empowerment intervention was carried out for two weeks. Data collection was carried out between November 2023 and March 2024. The sample in this study was families who had parents with hypertension who were still actively working. The minimum total sample recruited was 120 for each group. The results of the study, the family empowerment program had positive results compared to the control group at T1 in two areas: the quality of life score showed a slight increase of 2.07 points (95% CI 1.27 to 4.12). At T2, there was a significant increase in quality of life compared to the control group, with a DID coefficient of 3.08 and a 95% confidence interval ranging from 1.42 to 7.13. Conclusion, the implementation of family empowerment improves the quality of life of elderly people with hypertension who are still actively working Keywords: family empowerment, quality of life, elderly, hypertension